Outcomes of COVID-19 related hospitalization among people with HIV in the ISARIC WHO Clinical Characterization Protocol (UK): a prospective observational study. - Geretti,AM; Stockdale,AJ; Kelly,SH; Cevik,M; Collins,S; Waters,L; Villa,G; Docherty,A; Harrison,EM; Turtle,L; Openshaw,PJM; Baillie,JK; et al. (Clinical Infectious Diseases, 2020)
BACKGROUND: Evidence is conflicting about how HIV modulates COVID-19. We compared the presentation characteristics and outcomes of adults with and without HIV who were hospitalized with COVID-19 at 207 centers across the United Kingdom and whose data were prospectively captured by the ISARIC WHO CCP study. METHODS: We used Kaplan-Meier methods and Cox regression to describe the association between HIV status and day-28 mortality, after separate adjustment for sex, ethnicity, age, hospital acquisition of COVID-19 (definite hospital acquisition excluded), presentation date, ten individual comorbidities, and disease severity at presentation (as defined by hypoxia or oxygen therapy). RESULTS: Among 47,592 patients, 122 (0.26%) had confirmed HIV infection and 112/122 (91.8%) had a record of antiretroviral therapy. At presentation, HIV-positive people were younger (median 56 versus 74 years; p<0.001) and had fewer comorbidities, more systemic symptoms and higher lymphocyte counts and C-reactive protein levels. The cumulative day-28 mortality was similar in the HIV-positive vs. HIV-negative groups (26.7% vs. 32.1%; p=0.16), but in those under 60 years of age HIV-positive status was associated with increased mortality (21.3% vs. 9.6%; p<0.001 [log-rank test]). Mortality was higher among people with HIV after adjusting for age (adjusted hazard ratio [aHR] 1.47, 95% confidence interval [CI] 1.01-2.14; p=0.05), and the association persisted after adjusting for the other variables (aHR 1.69; 95% CI 1.15-2.48; p=0.008) and when restricting the analysis to people aged <60 years (aHR 2.87; 95% CI 1.70-4.84; p<0.001). CONCLUSIONS: HIV-positive status was associated with an increased risk of day-28 mortality among patients hospitalized for COVID-19.